Konservasi Koleksi Lukisan Museum Le Mayeur - Suparma Netra, I Made; Wardi, Nyoman (Humanis; Vol 23 No 3 (2019)DO - 10.24843/JH.2019.v23.i03.p08, 2019)
As a result of human work, painting is a cultural heritage that has important values. The state of the structure of the paintings which is composed by organic materials makes the painting very vulnerable to the environmental influences and other causes of damage. This research aims to find out about the characteristics of the painting, the types of damage, the factors that cause damage, and its conservation techniques both preventive and and curative to painting collection of Le Mayeur Museum. The results of this research are expected to provide benefits and development of science in the field of archeology about the study of cultural heritage conservation. This study uses qualitative analysis, technology analysis, and comparative analysis. Data collection technique used are direct observation technique, interviews, and library reserach studies. The theories applied  are Aesthetic Theory and Conservation Theory. The results obtained namely the characteristic of Le Mayeur’s paintings are representative with women’s theme and surroundings life, the coloring technique using plaque technique with oil paint, watercolor, traditional paint, and pastels color. Generally, there are several types of damage to the painting collection of Le Mayeur Museum, such as physical or mechanic damage, biotic damage, and chemical damage. Those types of damage are caused by physical factors,chemistry factors, biotic factors, and human factors. The conservation techniques carried out at the Le Mayeur Museum include preventive conservation and curative conservation. The preventive actions are carried out with control of temperature, air humidity, intensity of ultraviolet light, and control of air containing salt due to sea water vapor. The curative actions taken are semi-chemist medicine and painting restoration.